Analysis of Role of Bowel Preparation in Colorectal Surgery (Medical Forum Monthly, 2021)
Objective: An important goal of this study is analyzing bowel preparation’s role in process of colorectal surgery among local population of Pakistan.Study Design:Place and Duration of Study: This study was conducted at the DHQ Teaching Hospital Gujranwala during January 2019 till June 2019.Materials and Methods: Incidental colorectal cancer with minimal BRBPR, can be taken as minute quantity of RBCs in post wiping conditions or small quantity of blood drops in the post defecation conditions. There were small quantities of blood over the stool and they are also considered as minimal BRBPR. The blood that was mixed in stool was not considered as minimal BRBPR. All patients were interviewed and examined by a gastroenterologist.Results: No effected person was with zero symptoms when he went to seek medical assistance. About 60% of total 81 person were experiencing rectal bleeding. Apart from rectal bleeding, the most common symptoms were reported by 20% or more of the sample, they were some changes in habits of bowels (65%), stress and fatigue (47%), painful conditions (35%), loss of weight (21%), and general type of indisposition (20%). There were some rare symptoms that were reported including feeling dizziness (13.2%), appetite loss or nausea (11.8%) and Temperature or fever (5.2%).Conclusion: It is concluded effected person who were experiencing the situation of rectal bleeding were seen to be longer patient intervals while in contrast to it patients who were not suffering from rectal bleeding while controlling for the influence regarding possible or feasible confounders as well as other most common symptoms that were reported.